Fauna Europaea: Mollusca – Bivalvia - Rafael Araujo; Yde de Jong (Biodiversity Data Journal, 2015)
Fauna Europaea provides a public web-service with an index of scientific names (including important synonyms) of all living European land and freshwater animals, their geographical distribution at country level (up to the Urals, excluding the Caucasus region), and some additional information. The Fauna Europaea project covers about 230,000 taxonomic names, including 130,000 accepted species and 14,000 accepted subspecies, which is much more than the originally projected number of 100,000 species. This represents a huge effort by more than 400 contributing specialists throughout Europe and is a unique (standard) reference suitable for many users in science, government, industry, nature conservation and education. For the Mollusca-Bivalvia, data from 5 families (Margaritiferidae, Unionidae, Sphaeriidae, Cyrenidae, Dreissenidae) containing 55 species are included in this paper. European freshwater bivalves belong to the Orders Unionoida and Cardiida. All the European unionoids are included in the superfamily Unionoidea, the freshwater mussels or naiads. The European cardiids belong to the following three superfamilies: Cardioidea, Cyrenoidea and Dreissenoidea. Among the Unionoidea there are the most imperilled animal groups on the planet while the Cardioidea includes the cosmopolitan genus Pisidium, the Cyrenoidea the Asiatic clam (Corbicula fluminea) and the Dreissenoidea the famous invasive zebra mussel (Dreissena polymorpha). Basic information is summarized on their taxonomy and biology. Tabulations include a complete list of the current estimated families, genera and species.